Adam's ancestors: race, religion, and the politics of human origins - Livingstone, David N. (Medicine, science, and religion in historical context, 2011)
Beginnings : questioning the mosaic record -- Heresy : Isaac La Peyrre and the pre-adamite scandal -- Polity : the cultural politics of the adamic narrative -- Apologetics : pre-adamism and the harmony of science and religion -- Anthropology : Adam, adamites, and the science of ethnology -- Ancestors : evolution and the birth of Adam -- Bloodlines : pre-adamism and the politics of racial supremacy -- Shadows : the continuing legacy of pre-adamite discourse -- Dimensions : concluding reflections